Vinegar (acetic acid) intake on glucose metabolism: A narrative review. (August 2019) - Santos, Heitor O.; de Moraes, Wilson M.A.M.; da Silva, Guilherme A.R.; Prestes, Jonato; Schoenfeld, Brad J.
Summary: Vinegar intake is considered a food item that improves blood glucose in humans. This review aimed to discuss studies that investigated the impact of vinegar intake on the glycemic profile in humans and the putative mechanistic cellular pathways in both human and animal models. A search of literature was performed on the Cochrane, MEDLINE and Web of Science databases for articles published between 1995 and 2018. There is considerable support for vinegar having a positive acute effect on blood glucose levels when combined with carbohydrate-rich meals. Conversely, there are few chronic interventions analyzing the impact of vinegar intake on blood glucose. Based on available evidence, we hypothesize three pathways by which vinegar may improve blood glucose: The inhibition of α-amylase action; increased glucose uptake; and mediation by transcription factors. When evaluating the current body of literature, daily vinegar intake in amounts of ∼10–30 mL (∼2–6 tablespoons) appear to improve the glycemic response to carbohydrate-rich meals; however, there is a paucity of studies investigating chronic effects of vinegar intake. Graphical abstract: Image 1 Highlights: Vinegar (acetic acid) intake improves acutely the glucose metabolism. The effects occur manly in subjects with type 2 diabetes mellitus. There are few interventions based on follows-up. 10–30 mL/d (∼2–6 tablespoons) of vinegar is the more studied dose.